2014
DOI: 10.1186/1477-7819-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Femur performed better than tibia in autologous transplantation during hemipelvis reconstruction

Abstract: BackgroundPelvic reconstruction after hemipelvectomy can greatly improve the weight-bearing stability of the supporting skeleton and improve patients’ quality of life. Although an autograft can be used to reconstruct pelvic defects, the most suitable choice of autograft, i.e., the use of either femur or tibia, has not been determined. We aimed to analyze the mechanical stresses of a pelvic ring reconstructed using femur or tibia after hemipelvectomy using finite element (FE) analysis.MethodsFE models of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 26 publications
(23 reference statements)
1
41
0
Order By: Relevance
“…For the treatment of bone defects after type III hemipelvectomy, more and more surgeons tend to reconstruct defect because of the reported complications. Up to now, allograft, mesh repair and arti cial ligament repair are the main choices for reconstruction after type III hemipelvectomy (11,12,16). Recent reconstruction ways after type III resection were listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of bone defects after type III hemipelvectomy, more and more surgeons tend to reconstruct defect because of the reported complications. Up to now, allograft, mesh repair and arti cial ligament repair are the main choices for reconstruction after type III hemipelvectomy (11,12,16). Recent reconstruction ways after type III resection were listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some reconstruction methods have been reported after type III hemipelvectomy, including allograft, mesh and arti cial ligament (11,12). However, large amount of studies revealed various limitations of these reconstruction options.…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal excision was described for lesions higher on the anterior wall of the rectum, with the advantage of avoiding anal dysfunction [ 5 ]. Another method for the resection of these tumours was the perineal approach, which was implemented for GIST in the anterior wall of the rectum in some case reports [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gangping et al. [18] analyzed 116 patients with rectal cancer who underwent transanal excision and concluded that TAE for rectal cancer is satisfactory for T1 stage tumors, but it is not suitable for T2 stage tumors due to the high local recurrence rate in T2 lesions (6% vs. 15%, respectively).…”
Section: Discussionmentioning
confidence: 99%